Challenges and opportunity in the era of quantitative echocardiography. Issue 4 (December 2017) - Yu, Cheuk-Man
Abstract : The advancement of echocardiography in the past two decades is more than downsizing of the machines and improvement of image quality, but introduction of new imaging modalities leading to the ability of performing quantitative analysis. This function is greatly facilitated by the integration of echo machines with high performance computers, software programming and establishment of workstation for offline analysis. Today, echo examination is more than estimation of ejection fraction (EF) and patterns of left ventricular (LV) diastolic dysfunction. Echosonographers are facing a large number of quantitative parameters for interpretation. In newer imaging modalities such as tissue Doppler imaging, speckle tracking, 3-dimensional echocardiography and 3D-transoesophageal echocardiography, quantitative echocardiographic assessment has important roles. These have brought many opportunities but also challenges in our echo practice.